Effectiveness of Adding Extruded Wheat Straw to Poultry Manure to Increase the Rate of Biogas Yield - Polishchuk V.М.; Shvorov S.А.; Zablodskiy М.M.; Kucheruk P.P.; Davidenko T.S.; Dvornyk Ye.O. (Problems of the Regional Energetics, 2021)
The work is aimed at increasing the biogas yield rate at biogas plants by means of co-digestion poultry manure in combination with extruded wheat straw. To achieve this goal a series of batch tests were performed to study the yields of biogas and CH4 in anaerobic fermentation of mixtures of manure with extruded wheat straw. The working hypothesis of the study was that the wheat straw addition would allow optimizing carbon to nitrogen ratio reducing thus the inhibitory effect of ammonium nitrogen contained in poultry manure on the digestion process. The most important result of the study consisted in the development of a methodology for determining the efficient ratios of extruded straw to poultry manure, at which the highest rate of methane yield was ensured. The two series of the batch assays at 36°C were performed to study the effect of the straw addition to chicken manure at high and low initial volatile solids concentrations. In each series, three types of mixtures were prepared – with 100%, 65% and 35% of poultry manure by volatile solids content in the combination with wheat straw pellets. The significance of the research results was in the fact that the use of extruded straw together with chicken manure could increase the rate of methane yield by almost two times, compared to the fermentation of only poultry manure. The positive effect of wheat straw addition to poultry manure was found in mixtures with a high initial volatile solids concentration, and hence, a high concentration of nitrogen.